ANALISIS PERTIMBANGAN HAKIM DALAM PERALIHAN HAK ATAS TANAH TERLANTAR MILIK BADAN USAHA MILIK NEGARA NOMOR : 03/PDT.G/2011/PN-LSM” - Nurmalinda N; Sulaiman S; herinawati H (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2021)
Abandoned land is land that has been granted rights by the state in the form of Ownership Rights, Business Utilization Rights, Building Use Rights, Use Rights and Management Rights, or basic control over land that is not cultivated, not used, or not utilized in accordance with the circumstances or the nature and purpose. granting rights or the basis for their control. The definition of abandoned land is not regulated in Government Regulation of the Republic of Indonesia Number 11 of 2010 concerning Control and Utilization of Abandoned Land (“PP No. 11/2010”). However, it is regulated in Article 1 point 6 of the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 4 of 2010 concerning Procedures for Controlling Abandoned Land.The results of the study explain that the judge with his considerations in the case related to the transfer of rights to abandoned land belonging to state-owned enterprises in the decision Number: 3/Pdt.G/2011/PN-Lsm The judge considered that the problem in the abandoned domain was absolutely not the authority of the lhokseumawe district court. However, in the State Administrative Court, because the plaintiff in his case mentioned the ownership assets of the land. Thus, the judge rejected all of the plaintiffs' claims.